EXPERIMENTAL OBSERVATIONS ON THE BEHAVIOR OF A PILED RAFT FOUNDATION (Journal of Engineering, 2011)
The piled raft is a geotechnical composite construction consisting of three elements: piles, raft and soil.In the design of piled rafts, the load shared between the piles and the raft, and the piles are used up to aload level that can be of the same order of magnitude as the bearing capacity of a comparable singlepile or even greater. Therefore, the piled raft foundation allows reduction of settlements in a veryeconomic way as compared to traditional foundation concepts.This paper presents experimental study to investigate the behavior of piled raft system in sandysoil. A small scale “prototype” model was tested in a sand box with load applied to the system througha compression machine. The settlement was measured at the center of the raft, strain gages were usedto measure the strains and calculate the total load carried by piles. Four configurations of piles (2x1,3x1, 2x2 and 3x2) were tested in the laboratory, in addition to rafts with different sizes. The effects ofpile length, pile diameter, and raft thickness on the load carrying capacity of the piled raft system areincluded in the load-settlement presentation.It was found that the percentage of the load carried by piles to the total applied load of thegroups (2x1, 3x1, 2x2, 3x2) with raft thickness of 5 mm, pile diameter of 9 mm, and pile length of 200mm was 28% , 38% , 56% , 79% , respectively. The percent of the load carried by piles increases withthe increase of number of piles.